Tipe Kepribadian Berbasis Pumping HR Model Terhadap Sasaran Kerja Pegawai Negeri Sipil Dinas Pertanian Kota Bogor - Suherbi, Didong; Juwaini, Ahmad; Ramly, Amir Tengku (Jurnal Manajemen, 2020)
Good governance is a set of processes that are implemented in an organization to make a decision. Human self can not be separated from the so-called personality. Personality is a dynamic organization of individual psycho-physical systems. Personality determines individual behaviour and thinking in a unique way. Personality is the best factor to be used to predict employee performance. Civil Servants (PNS) who have introverted and extroverted personalities can influence performance. The measured performance consists of Employee Work Objectives (SKP) and Attitude. This study aims to examine the effect of personality on SKP and Attitude. The method used is the ANOVA, BNT and dummy regression tests. The sample was measured by 40 non-random sampling techniques. The results showed that the Extrovert = introvert personality type gives a greater influence on SKP. Extrovert = introvert personality type has a greater influence on Attitude. There is a significant difference between personality types with SKP. There is a significant difference between personality types with Attitude. Extrovert = Introvert personality type produces the best average of work performance (SKP and Attitude). Whereas Extrovert personality types produce the lowest average on work performance (SKP and Attitude) of Civil Servants, Bogor Agriculture Department. To produce good work performance in an SKPD (Regional Work Unit), it is preferred to place extrovert = introvert personality types, especially in important positions.